Geochemistry of artificial groundwater recharge into the Kopoasfontein breccia pipe near Calvinia, Karoo - Cave, Lisa Caryn (Department of Geological Sciences, 2024)
Artificial groundwater recharge has been proposed as an innovative strategy for managing the scarce water supplies of the town of Calvinia, near the edge of the Karoo, South Africa. Surplus runoff water from the town dam or groundwater from boreholes in weathered shale aquifers would be injected into the Kopoasfontein breccia pipe, a roughly cylindrical body of fractured rock, 12 km east of the town. Subsurface water storage would then mjnjmjse evaporative losses, so that the injected water could be recovered when emergency water supplies are needed. Underground storage space for an estimated 70 000 m3 of water is available in the natural fractures and cavities of the breccia, but the unusual geochemistry of the breccia pipe system promises to be a controlling factor affecting the viability of the scheme. A geochemical investigation of the rocks from Kq,oasfontein and the various water sources has revealed substantial differences in composition, pH and redox status between the brcccia pipe, Karoo groundwater and surface water sys=m. Major rock types in the upper portion of the breccia pipe are baked, fragmented mudstoncs and shales, which have been subjected to hydrothermal alteration. Base cations in the rock are dominated by K, Mg and Na, but Ca concentrations are generally low. There is a trend of inaeasing Na and· decreasing K with depth over the upper 400 m of the brcccia pipe. The major mineral phases in the bulk rock are quartz, feldspar and clays from the illite, chlorite and kaolinite groups. Late stage secondary minerals have also been deposited in the brecciated shale environment by hydrothermal solutions. Quartz, calcite, chlorite and ~tal sulphide minerals (pyrite, pyrrhotite, chalcopyrite, galena) occur as vein minerals in the breccia and as coatings on the walls of fractures and cavities. Well-formed crystals of the subzeolite mineral, fluorapophyllite, line many of the breccia cavities. Toe hydrothermal minerals generally occur along the zones of weakness, which are also the regions of highest permeability. Reaction with these minerals is likely to control the composition of groundwater in the Kopoasfontein pipe. Groundwater from Kopoasfontein is characterised by low salinity (EC = 70 mS/m), high pH (9.8) and the presence of species such as NH/. H2S and possibly CH4, which indicate a strongly reducing environment. The water is of Na-Cl type, but HCO3- and co/- are also important anions in solution. High concentrations of p- (12 mg/L) and As (0.33 mg/L) pose a health risk for long term consumers of this water and could become a problem if similar levels were to develop in water stored for emergency supply. Average concentrations of F (360 mg/kg} and As (11 mg/kg} in the Kopoasfomein rocks are not abnormally high for shales, but the geochemical environment favours mobilisation of P-- and HzAsO3- in the groundwater. Dissolution of fluorapophyllite is proposed as a viable source of p- in the Kopoasfontein breccia in the absence of measurable fluorite. Fluoride concentrations are gen!rally limited by the solubility of CaF2, but low Cal+ (5.3 mg/L), due to low CaCO3 solubility at high pH and possibly base cation exchange of Ca2+ for Na+ on mineral surfaces, has allowed high pconcentrations to accumulate. Alkaline conditions also favour the exchange of OH- for padsorbed to aquifer surfaces. Under reducing conditions As(Ill) forms arsenite oxyanions which have higher mobility than the oxidised arsenate forms, particularly at high pH when iii anion adsorption is low. The water sources proposed for recharge have vastly differing chemical characteristics. Groundwaters from the Karoo aquifers are hard (1400 to 3090 mg/Las CaCOJ, brackish (EC := 400 to 770 ~/m) and have near neutral pH (J .4 to 7. 7). The dominant ions are Na+, Mg2+ and ci-. Saturation index calculations indicate that the groundwaters are likely to be in equilibrium with respect to Ca and Mg carbonates, and precipitation of these minerals may occur under conditions of increased pH or decreased CQi partial pressure. The high salinity makes these waters generally unsuitable as a domestic water source or for artificial recharge, unless they can be desalinated or blended with low salinity waters. Surface water, by contrast, is of very high quality, with low EC ( ~ 18 ~/m) and neutral pH (7.6 untreated; 7.2 treated). The dominant ions are Ca2+, Mg2+ and HCO3-. Suspended particulates and IX>C (6.6 mg C/L after treatment) pose a risk of clogging or biofouling if used for artificial rccbarge without effective treatment and filtration. Redox buffering, by dissolved oxygen in the smface water, may result in the oxidation of some of the reduced species in the breccia pipe, hit the pH buffering capacity of the surface waters is low and high pH is likely to result from reaction with the rocks and groundwater of Kopoasfontein. Groundwater from the Witwal breccia pipe provides an alternative recharge source which is compatible with the Kopoasfontein groundwater, because of its similar geological origin. This water has a slightly lower pH (8.8) and higher alkalinity (200 mg/Las CaCOJ than the Kopoasfontein groundwater and is of Na-Cl/HCO3'CO3 type. Witwal grwndwater also contains P- (2. 7 mg/L) which would require treatment after recovery from the breccia pipe. Using PHREEQC geochemical modelling software to simulate mixing of the water sources with the Kopoasfontein groundwater, blended waters are calculated to be supersaturated with respect to carbonate and ferric solids under oxidising conditions. Total iron COCK:Cntrations, and hence the quantities of ferric solid that may precipitate are, however, low. Calcite precipitation poses a potential risk for encrustatim of pipelines and plugging of breccia fractures if the CO2 partial pressure is too low to solubilise this mineral. Calcium in the Karoo groundwaters also created supersaturated conditions with respect to fluorite for simulated mixtures with Kopoasfontein groundwater. Fluorite precipitation could be expected to partially remove pfrom solution, provided Ca2+ is not completely precipitated out by calcite. Water-leachable components in the Kopoasfontein rocks are dominated by Na+, K+ and alkalinity. Batch-type leaching tests, which reacted powdered rock samples(~ 300# particle size) from Kopoasfontein with deionised water (water-rock ratio = 10: 1), produced solutions with a strong Na/K-HCO3'CO3 signature and an average pH of 9.4 after 124 hours. The highest p- concentration (3.6 mg/L) was leached from a sample rich in tluorapophyllite. The rock material contains substantial reserves of K+ and NH,.+ which are immobilised in the natural system, but have been released to solution in laboratory experiments, enhanced by the action of crushing the rock. Concentrations of 61 mg/L K+ and 9. 9 mg/L NH,.+ were measured in a solution of EC 51 mS/m and pH 8.3 after 350 hours reaction of deionised water with powdered rock ( - 300# particle size; water-rock ratio = 3: 1). Increasing the size of the rock particles produced a decrease in K+, NH,.+ and alkalinity and an increase in so/- and p-. iv Concentrations of S.4 mg/L p- and 270 mg/L s0.2- were measured in a solution of EC 62 mS/m and pH 7 .S when coarser rock samples (2-10 mm particle si2:c), containing a higher concentration of hydrothermal vein minerals, were reacted with deionised water (water-rock ratio= 3:1) for S17 hours. A trend of decreasing pH during all batch experiments is partially attributable to CO2 dissolution in an uncontrolled atmosphere, but processes of sulphide mineral oxidation and nitrification of ammonium have also produced acidifying effects. Solubilisation of calcium and magnesium solids resulted in higher ea2+ and Mg1+ con;emrations in solutions with lower pH. Reaction of surface water with the Kopoasfontein rock led to similar solution composition to those of the leaching tests (Na/K-HCO/COJ. Karoo groundwater composition, however, was little changed by reaction with the rock, because of the high solute concentrations in the original waters. These groundwaters showed an increase in K+ and NH4 +, but a small amount of Na+, ca2+, Mg2+ and even er were removed from solution. The average pH of 8.2 for the Karoo groundwaters after equilibration with the rock is consistent with pH buffering by precipitation of CaC03• High salinity in these waters may also inhibit nitrification of NH4 + released from the rock. Fluoride and arsenic concentrations in K.opoasfontein groundwater were found to be almost halved in a batch test reaction with the powdered rock sample. Oxidising conditions (pe i:: +4.S), decreased pH (8.4) and exposure of a large mineral surface area for adsorption in the powdered rock sample may have all contributed to the partial immobilisation of these constituents. The constraints of working under laboratory conditions may limit the direct application of these findings to the field situation. The groundwater flow conditions, water-rock contact area, resideI¥:C times, mixing ratios, pressure, temperature and gas composition in the subsurface are all factors which have not been quantified and may influence the quality of recovered water or loss of permeability in the artificial recharge scheme. The addition of p-, As and possibly K+ and NH4 + to waters stored in the Kopoasfontein breccia is likely to cause problems for the managers of the artificial recharge scheme, the severity of which will depend on the duration of storage and geochemical conditions in the subsurface. Decreasing pH and the introduction of oxidising agents may help to control P- and As concentrations and prevent CaC03 precipitation, but will also favour nitrification of NH4 + to No2- or N~- and the generation of so/- from sulphide mineral oxidation. Monitoring of these parameters during pilot injection experiments may help to identify problems at an early stage so that they can be addressed before valuable water resources are lost.